The Effect of Midline Exercise Therapy on Global Delayed Development Children’s Gross Motor - Khabib Abdullah; Atik Swandari; Rita Vivera Pane; Akhmad Muzamil; Anik Muwarni Darajatun (GLOBAL HEALTH SCIENCE GROUP, 2024)
Global delayed development (GDD) is a developmental disorder in children characterized by delays in gross motor development. Gross motor development is based on the development of an optimal midline position, and in GDD this does not happen. This reseaarch objective to determine the effect of midline exercise therapy on improving gross motor skills in children with GDD at Haji Hospital Surabaya. This is experimental research purposive sampling research on 15 GDD children at RSUD Haji Surabaya with a one-group pre and post-test design. Midline exercise therapy is carried out twice a week for 6 weeks consisting of relaxing the neck extensors, adjusting the position to the middle of the body, and cortical level exercises. Tool for measuring children's gross motor skills with GMFM (gross motor functional measurement) sector A/lying down with scale 0-51 measured pre and post treatment. Data analysis with univariate and bivariate SPSS. For the results 3 subjects were boy and 12 girl with an average age of 13.1 months. There was an increase in the mean GMFM score from 4.2 to 6 (paired t-test p=0.000) after 12 physiotherapy sessions.